Sino-Malay trade and diplomacy from the tenth through the fourteenth century - Heng, Derek Thiam Soon (Research in international studies. Southeast Asia series, 2009)
China has been an important player in the international economy for two thousand years and has historically exerted enormous influence over the development and nature of political and economic affairs in the regions beyond its borders, especially its neighbors. Sino-Malay Trade and Diplomacy from the Tenth through the Fourteenth Century examines how changes in foreign policy and economic perspectives of the Chinese court affected diplomatic intercourse as well as the fundamental nature of economic interaction between China and the Malay region, a subregion of Southeast Asia centered on the S.